2011
DOI: 10.1371/journal.pone.0029134
|View full text |Cite
|
Sign up to set email alerts
|

Kv4.2 Mediates Histamine Modulation of Preoptic Neuron Activity and Body Temperature

Abstract: Histamine regulates arousal, circadian rhythms, and thermoregulation. Activation of H3 histamine receptors expressed by preoptic GABAergic neurons results in a decrease of their firing rate and hyperthermia. Here we report that an increase in the A-type K+ current in preoptic GABAergic neurons in response to activation of H3 histamine receptors results in decreased firing rate and hyperthermia in mice. The Kv4.2 subunit is required for these actions in spite of the fact that Kv4.2−/− preoptic GABAergic neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Our experiments have also revealed that histamine modulation of the activity of GABAergic PO/AH neurons provides a mechanism for selective modulation of body temperature at the beginning of the active phase of the circadian cycle [61]. Thus, injection of a H3 antagonist in the MnPO induces a delay in the onset of the rise of the body temperature associated with the active phase of the circadian cycle [61].…”
Section: Central Histaminergic Modulation Of Core Body Temperaturementioning
confidence: 53%
See 2 more Smart Citations
“…Our experiments have also revealed that histamine modulation of the activity of GABAergic PO/AH neurons provides a mechanism for selective modulation of body temperature at the beginning of the active phase of the circadian cycle [61]. Thus, injection of a H3 antagonist in the MnPO induces a delay in the onset of the rise of the body temperature associated with the active phase of the circadian cycle [61].…”
Section: Central Histaminergic Modulation Of Core Body Temperaturementioning
confidence: 53%
“…Histamine applied in the MnPO nucleus induced a robust, long-lasting hyperthermia effect that was mimicked by H3 histamine receptor subtypespecific agonists [21]. We have also established that an increase in the A-type K + current in GABAergic MnPO neurons in response to activation of H3 histamine receptors results in decreased firing rate and hyperthermia in mice [61]. The Kv4.2 subunit is required for these actions since Kv4.2-/-preoptic GABAergic neurons are not affected by histamine or H3 agonists.…”
Section: Cellular Mechanisms Involved In Histamine Induced Hyperthermiamentioning
confidence: 56%
See 1 more Smart Citation
“…These effects may be partially unrelated to the block of Ca-ATPase, as thapsigargin from 200nM on blocks voltage-gated calcium channels (Shmigol et al, 1995), which are known to undergo partial blockade after H 3 R activation (Takeshita et al, 1998). Further signaling pathways activated by H 3 R in histamine neurons await characterisation and may employ modulation of K+ currents (Lundius et al, 2010;Sethi et al, 2011;Zhou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, Kv4.2−/− GABAergic preoptic neurons present identical firing properties with w-t neurons although they have reduced A-type currents (in spite of compensatory upregulation of the Kv4.1 subunit) [7]. However, these neurons also present a robust upregulation in the delayed rectifier current (I DR ) [7]. In order to gain further insights in the mechanisms of electrical remodeling in preoptic neurons, in this study we have determined the molecular nature and the electrophysiological properties of the increased I DR of Kv4.2−/− GABAergic preoptic neurons to test the hypotheses that the upregulation involves a specific Kv channel subunit and that it is responsible for the conserved firing characteristics of Kv4.2−/− neurons.…”
Section: Introductionmentioning
confidence: 94%